Engaging the Silent Learners: Pedagogical Strategies for Supporting Introverted EFL Learners in the Classroom - Zulfikar Zulfikar; Sri Wahyuni Hasibuan; A’zizah A’zizah; Rahmati Rahmati; Dina Syarifah Nasution (Tamaddun Life, 2024)
Despite the critical role of personality in academic success, schools frequently overlook the unique needs of introverted students in EFL classrooms, where tailored instructional strategies can significantly improve their engagement and understanding. This study builds on prior research that primarily examined speaking instructions, highlighting the overlooked instances of introversion in various skill-specific classrooms. It examined the pedagogical strategies employed by teachers in a classroom with introverted EFL learner minority. The primary objective of this study is to identify the challenges faced by the teachers, the various strategies they employed to accommodate the unique learning needs of introverted EFL learners in the context of English language learning, as well as the effectiveness of the strategies from the perspectives of the teachers. Employing a qualitative research design, this study utilized purposive sampling to select the participants and collected the data through interviews with three English teachers at MTsN 1 Mandailing Natal. The findings revealed that during the instructional process, the teachers encountered several challenges in effectively engaging with introverted learners, which include the introvert EFL learners’ lack of interest in engaging in the class activities and their limited mastery of vocabulary. The findings also disclosed a set of strategies that can support introverted learners, including modeling, small-group discussions, game-based instruction, autonomous study, and peer teaching. All participants expressed positive perceptions regarding their learners’ experiences teaching introverted learners, suggesting the effectiveness of these strategies in enhancing the motivation of introverted learners and achieving educational objectives. The study highlights the imperativeness for educators to thoughtfully consider diverse characteristics of introverted students to foster their motivation within the classroom environment by exerting considerable effort to stimulate engagement from introverted EFL learners within the classroom setting.